Evaluation of the knowledge, attitudes, and behaviors of school-age children on oral and dental health - Yıldız, Semsettin; Ataş, Osman (MediHealth Academy Yayıncılık, 2024)
Aims: It is essential to teach children behaviors about oral and dental health in the early period. This study aimed to evaluate school-age children's knowledge, attitudes, and behaviors about oral and dental health. Methods: The population of this research consists of 782 school-age literate individuals who applied to the Fırat University Faculty of Dentistry Department of Pedodontics. A questionnaire consisting of 20 questions was administered to the participants. Results: 45.5% of the participants were boys, and 54.5% were girls. The mean age of the participants was 10.53±1.95. While 42.7% of the participants answered in the morning and before going to bed, 24.7% stated that they did not brush regularly. The rate of those who indicated that they touched only in the morning was 11.6%, and those who said that they brushed only in the evening was 21.6%. Also, "When do you brush your teeth?" there is a significant difference in the answers given among the participants based on their gender (p<0.05). The female participants answered that they brush their teeth in the morning and before bed at a higher rate than the male participants. In addition, 77.9% of the female and 70.5% of the male participants think that routine dental check-ups should be done before our teeth hurt. Conclusion: As a result of this study, it was seen that the individual's knowledge, attitudes, and behaviors on oral and dental health were similar to other studies in the literature. We think the behaviors taught to school-age children about oral and dental health can be effective throughout an individual's life.
Keywords: Paedodontics; Çocuk Diş Hekimliği